Serum-free placental growth factor isoform 1 at 11-13-week gestation: effects of maternal factors, mean arterial pressure, placental volume, and uterine artery pulsatility index - Bhuwapathanapun, Maolee; Pratumvinit, Busadee; Lahfahroengron, Piyaporn; Hanyongyuth, Sithikan; Phaophan, Amprapha; Pooliam, Julaporn; Wataganara, Tuangsit (The journal of maternal-fetal & neonatal medicine, 2018)
To define the effects of maternal factors, mean arterial pressure (MAP), placental volume (PV), and uterine artery Doppler pulsatility index (UtAPI) to serum level of free form of placental growth factor isoform 1 (free PlGF-1) measured with a novel automated assay. We enrolled 200 Thai women singleton pregnancy from 11 to 13 weeks gestation with low prior risk maternal factors (age, parity, tobacco use, assisted reproductive technology, and body mass index). MAP was measured. Serum-free PlGF-1, PV, and UtAPI were measured with a new assay, transabdominal three-dimensional, and color Doppler ultrasounds, respectively. Effects of these variables to serum-free PlGF-1 level were assessed. Data from 195 eligible subjects showed an elevation of serum-free PlGF-1 from 11, 12, and 13 weeks (mean ± SD; 36.89 ± 24.92, 38.71 ± 17.44, and 49.68 ± 22.30 pg/mL, respectively (p < .05)). Serum-free PlGF-1 level showed positive correlation with PV (r = 0.290, p < .01), and negative correlation with right and left UtAPI (r = -0.717, p = .05 and r = -0.221, p < .05, respectively). PV showed negative correlation with right and left UtAPI (r = -0.243, p < .05 and r = -0.372, p < .05, respectively). Serum-free PlGF-1 level had no significant correlation with maternal factors or MAP (p > .05). There was no preeclampsia at <34 weeks in 161 subjects (82.6%) with known pregnancy outcomes. There was modest correlation of serum-free PlGF-1, PV, and UtAPI, but not with maternal factors or MAP. Adjustment of serum-free PlGF-1 in early preeclampsia screening algorithm should be considered.